Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Teknik Instalasi Penerangan Listrik Rumah Sederhana Di SMKN 1 Darul Kamal - Akbarul Kautsar; Marzuki Marzuki; Sadrina Sadrina (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
This research is motivated by the low learning outcomes of students in subjects Simple home electric lighting installation techniques, this is because the learning process is still teacher-centered. This study aims to reveal differences in student learning outcomes between jigsaw cooperative learning models with conventional models in subjects of simple home electric lighting installation techniques at SMK 1 Darul Kamal and to improve student learning outcomes. The research method used was Pre-Experiment with the research subjects of the 11th grade students of TITL SMKN 1 Darul Kamal consisting of 1 class, students were divided into 2 groups, namely the experimental group and the control group. From the results of data analysis based on the results of the t-test shows that Ho is rejected based on the significance value <α = 5% or 0.05, in the column t-test for equality of means we see in the column "sig. 2 tailed "with Equal variances assumed, the variance similarity test was obtained that both control and experimental groups had the same variant. Value "sig. 2 tailed "that is: 0.00 then it can be decided that Ho is rejected because the sig value is 0.00 <α = 0.05, so it can be concluded at the significance level (α) = 5% the control group and the experimental group do not have the same average value. So that the truth is that there are significant differences in student learning outcomes of the experimental group using the Jigsaw cooperative learning model compared to the control group students who did not use the jigsaw cooperative learning model.